Volatile Organic Compounds (VOCs) Distribution from PCB Waste and Vitrification by Reacting with Flux Agents - Raynard Christianson Sanito; Sheng-Jie You; Hsi-Hsien Yang; Ya-Fen Wang (Aerosol and Air Quality Research)
Abstract Resin, the part of printed circuit board (PCB) waste, consists of harmful elements and volatile organic compounds (VOCs) and can cause pollution, but it can also be potentially treated through vitrification. Hence, the purpose of this study is to investigate the distribution of VOCs and analyze the effects of different flux agent types, pyrolysis duration, flux agent ratio, and effect of different carrier gases to vitrify resin waste in an atmospheric-pressure microwave plasma reactor. The resins to the flux agents — shell powder, limestone and quartz sand ratio of 50:50 and 25:75 gave the best results for the vitrification compared to the ratio of 75:25 and control (absence of flux agent). Furthermore, the crystalline structures of CaCO3 and SiO2 dominated the final residue, and this confirmed the vitrification of the resin. Flux agents also can reduce the distribution of propylene and benzene from the plasma pyrolysis. A longer duration of the pyrolysis, a higher flux agent ratio and flux agent types can be recommended for plasma pyrolysis applications even though they have no significant impact on the inertization of the elements statistically. Shell powder is thus suggested as a cost-less flux agent which can create vitrification and inertization of the contaminants from resin in plasma discharges.